C–H⋯Cl− hydrogen bonds in solution and in the solid-state: HgCl2 complexes with cyclen-based cryptands. Issue 12 (30th January 2017) - Ikeda, Mari; Sah, Ajay Kumar; Iwase, Miki; Murashige, Rina; Ishi-i, Jun-ichi; Hasegawa, Masatoshi; Kachi-Terajima, Chihiro; Park, Ki-Min; Kuwahara, Shunsuke; Habata, Yoichi
Abstract : Structural evidence is reported for C–H⋯Cl − hydrogen bonds in solution and in the solid state of cyclen-based cryptands/HgCl2 complexes. Abstract : Structural evidence is reported for C–H⋯Cl − hydrogen bonds in solution and in the solid state of HgCl2 complexes with cyclen-based cryptands. These cyclen-based cryptands (1 ) and (2 ) are bridged by di- and triethylene glycol units, respectively, between two aromatic rings. The X-ray structure indicates that the2 /HgCl2 complex contains an acetonitrile molecule in the cavity.